Evaluating the landscape ecological risk based on GIS: A case‐study in the Poyang Lake region of China. (11th May 2021) - Xie, Hualin; Wen, Jiaming; Chen, Qianru; Wu, Qing
Abstract: Influenced by human activities, the largest freshwater lake in China, Poyang Lake is suffering from landscape degradation and increased ecological risks. However, the specific landscape ecological risk in Poyang Lake region remains unknown. The impact of land use change on landscape pattern and ecological risk around Poyang Lake has not been revealed. In order to analyze the spatio‐temporal distribution characteristics of landscape ecological risk in Poyang Lake region, this study constructed a landscape ecological risk index model based on GIS, geostatistics, and landscape ecology theory. The results show that: (a) all land use types in Poyang Lake region had been changed during the period 2010–2018. While large tracts of farmland and woodland were converted into construction land, farmland and woodland have seen the largest decrease and construction land has increased greatly. (b) On the whole, the low and medium‐low landscape ecological risk area accounted for about 60% of the total area, while high and medium‐high risk area increased during 2010–2018. The landscape ecological risk has seen a downward trend with increased low and medium‐low ecological risk areas during 2010–2018. Spatially, ecological risk in the core waters of Poyang Lake was higher, while in the surrounding waters was lower. (c) The landscape ecological risk in Poyang Lake Region in each period shown positive spatial correlation and tended to be spatially agglomerative. The high‐high risk clusters were mainly located in the core waters of the Lake area, while the low‐low risk clusters were mainly located far away from the core waters, including county and city areas. (d) In 2018, farmland, woodland, grassland, and unutilized land were dominated by medium and medium low risk, the landscape ecological risk in the water area was the highest, and that of construction land was the lowest. The decrease rate of ERI in water areas was the largest, indicating that the change of water area contributed the most to the reduction of landscape ecological risk. During the process of ecological risk management in Poyang Lake Region, attention should be paid to the changes of the water area's structure and quality.